2004
DOI: 10.1111/j.1365-2222.2004.01883.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of allergens secreted by Anisakis simplex parasite: clinical relevance in comparison with somatic allergens

Abstract: A.s. secretes allergens more potent than somatic antigens and should be used in the diagnostic procedures. These allergens are inactivated by the pepsin, which supports the theory that live larva is necessary to induce an allergic reaction in most of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
48
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 24 publications
2
48
0
2
Order By: Relevance
“…Consequently, it is expected that the immune response against Anisakis allergens from third-and/or fourth-stage larvae (L3/L4) occurs in response to two consecutive antigenic stimuli: (i) the excretory/secretory (ES) and cuticle antigens while the larvae is alive; and (ii) the cuticle and protease-resistant somatic and ES antigens, after the larvae die. Previous studies have shown that the Anisakis ES allergens are the most clinically important, as they are targeted by most of the anti-Anisakis IgE antibodies induced during infections by this parasite [12]. However, there are no data available to indicate whether these antigens stimulate the immune system only during the short period of time after infection in which the larvae remain alive, or also after the death of the larvae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is expected that the immune response against Anisakis allergens from third-and/or fourth-stage larvae (L3/L4) occurs in response to two consecutive antigenic stimuli: (i) the excretory/secretory (ES) and cuticle antigens while the larvae is alive; and (ii) the cuticle and protease-resistant somatic and ES antigens, after the larvae die. Previous studies have shown that the Anisakis ES allergens are the most clinically important, as they are targeted by most of the anti-Anisakis IgE antibodies induced during infections by this parasite [12]. However, there are no data available to indicate whether these antigens stimulate the immune system only during the short period of time after infection in which the larvae remain alive, or also after the death of the larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Another characteristic of Anisakis-induced allergy is that either the ES allergens [12] or the allergens stored inside dead larvae [13][14][15] when administered to previously sensitized patients by the oral route. These results suggest that: (i) immunization against clinically relevant Anisakis allergens is only possible during the course of an active infection; and (ii) that these allergens are destroyed during the digestion process.…”
Section: Introductionmentioning
confidence: 99%
“…These allergic reactions are thought to be mediated by IgE that is specific to A. simplex allergens (Audicana and Kennedy 2008). Recent evidence suggests that only the ingestion of live larvae, which attach themselves to the human gastric mucosa, can cause these reactions (Sastre et al 2000;Alonso-Gómez et al 2004;Baeza et al 2004). However, cases of Anisakis-associated hypersensitivity attributable to ingestion of cooked, canned, and frozen seafood have also been suggested in countries where Anisakis are endemic (Audicana et al 1997;Kameyama et al 2006;Audicana and Kennedy 2008).…”
mentioning
confidence: 99%
“…To date, seven A. simplex excretory-secretory (ES) allergens that were found to be thermostable or resistant to pepsin digestion have been reported. The patients, including allergic patients, develop specific IgE to these allergens (Baeza et al 2004;Audicana and Kennedy 2008;Pravettoni et al 2012). Oral challenges with lyophilized L3 or excretory-secretory extracts from L3 to sensitized patients who experienced several Anisakis-associated allergic reactions (urticaria, angioedema, anaphylaxis, or abdominal pain) after eating marinated, grilled or raw fish did not induce allergic manifestations (Baeza et al 2004;Sastre et al 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation